Design of a Smart Agri-voltaic system for irrigation purposes considering major crops - Hossain, Shoheb Abul; Ahmad, Kasshaf; Hossain, Md. Tamzid; Ariya, Afia Raidah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.